CLINICAL APPRAISAL OF ADMIT PIN FOR MANAGEMENT OF FEMUR FRACTURE IN SMALL ANIMALS. - Sharma, Mohit; Kumar, Adarsh; Tyagi, Som Prakash; Kumar, Amit (The Indian Journal of Animal Sciences, 2022)
The study included 27 femoral fractures treated using the Admit pinning technique in 25 client-owned dogs presented to the department of veterinary surgery and radiology at TVCC CSKHPKV, Palampur, HP. The fractures types included wedge (10), oblique (9), transverse (4), complex (3) and spiral (1). The status of fracture reduction and fixation was found to be good to excellent. All the dogs had excellent clinical outcome, except three cases which had an axial collapse of fracture after an episode of post-operative trauma, and 2 senile cases which showed delayed union (more than 60 days). Admit pinning, when used in conjuncture with orthopaedic wiring, can resist axial, bending, tension and torsional forces acting on the bone up to the level of no major complications.